ANALISIS PEMAHAMAN AKUNTANSI KOPERASI PADA KOPERASI PETANI SAWIT SUMBER REZEKI DESA KEPENUHAN RAYA - Arma Yuliza (Fakultas Ekonomi Universitas Pasir Pengaraian, 2015)
This study aims to determine the extent to which understanding of the cooperativesmallholders source of sustenance village highway districts fullness fullness of accountingcooperative. Collecting data in this study using interviews and analyzed descriptively.Results from this study is that the oil bonanza farmers' cooperative village fullness fullnesshighway districts that do not understand the accounting cooperative accounting has notbeen applied in preparing the financial statements cooperatives.